Women in fish production and post harvest in the island-town of Limasawa - Sumagaysay, Marieta B. (Iloilo City UP Visayas, 2004)
Women's work participation rates in coastal fisheries is usually on a "helping-out" role that is limited to the low-paying, menial jobs which are regarded as appendages to men's work. Their roles in the traditionally-male dominated fishing sector, nonetheless, are significant links in the whole fish production system. This paper looks into these roles, and the nature of women's work participation. Their contribution to fisheries utilization and management, specifically the "woman's voice' in fish production and post-harvest is identified.
Keywords: Commercial fishing -- Women